Graphic Novels in the School Library: Questions of Cataloging, Classification, and Arrangem - Becnel, Kim; Moeller, Robin A. (Knowledge organization, 2022)
In recent years, many school librarians have been scrambling to build and expand their graphic novel collections to meet the large and growing demand for these materials. For the purposes of this study, the term graphic novels refers to volumes in which the content is provided through sequential art, including fiction, nonfiction, and biographical material. As the library field has not yet arrived at a set of best practices or guidelines for institutions working to classify and catalog graphic novels, this study seeks to record the ways in which school librarians are handling these materials as well as issues and questions at the forefront of their minds. A survey of school librarians in the United States revealed that almost all of them collect fiction and nonfiction graphic novels, while 67% collect manga. Most respondents indicated that they are partly or solely responsible for the cataloging and classification decisions made in their media centers. For classification purposes, most have elected to create separate graphic novel collections to house their fictional graphic novels. Some include nonfiction graphic novels in this section, while others create a nonfiction graphic novel collection nearby or shelve nonfiction graphic novels with other items that deal with similar subject matter. Many school librarians express uncertainty about how best to catalog and classify longer series, adapted classics, superhero stories, and the increasing number and variety of inventive titles that defy categorization. They also struggle with inconsistent vendor records and past practices and suffer from a lack of full confidence in their knowledge of how to best classify and catalog graphic novels so that they are both searchable in the library catalog and easily accessible on the shelves.